Anxiety and Depression Levels with Risk Factors of Breast Cancer Patients in Erbil City - Iraq - Mosleh Saber Kareem; Diyar Hussain Taher (Hawler Medical University, 2021)
Background and objectives: Breast cancer appears to be becoming more common worldwide. It is the most common type of cancer in women in the Middle East and the Western countries. Patients with breast cancer are at a high risk of developing psychological problems such as anxiety and depression.  This study aimed to evaluate the severity of anxiety and depression levels in breast cancer patients and their risk factors for breast cancer. Methods: A quantitative descriptive study design was conducted at Rizgary Teaching Hospital and Nanakali Oncology Hospital in Erbil City in the Kurdistan Region of  Iraq from 1st September 2020 to 5th August 2021. The duration of data collection was four months and purposive sampling was used to select 298 patients who were admitted to both hospitals. A questionnaire format was used to gather the data, and the Hospital Anxiety and Depression Scale (HADS) standardized questionnaire was utilized to measure the level of anxiety and depression. Results: The average age of the patients was 45.28±9.17 years, 80.5% were married, 60.7% of the studied sample had a low socioeconomic status. Almost a third (30.5%) of the participants had severe anxiety and 60.4% had severe depression. Concerning the risk factors of breast cancer, 82.2% of patients were obese, 91.9% did not do exercise, 35.6% had breast cancer family history, 93.6% were non-smoker, and 6.4% of them were smokers. Conclusion: According to the findings, the majority of breast cancer patients suffer from anxiety and depression, and obesity is one of the risk factors for breast cancer.